2016
DOI: 10.1007/s10653-016-9847-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, enantiomeric signature and ecotoxicological risk assessment of HCH isomers and DDT metabolites in the sediments of Kabul River, Pakistan

Abstract: Hexachlorocyclohexane (HCH) isomers and dichlorodiphenyltrichloroethane (DDT) metabolites were analyzed in sediments of three different depths (0-10, 10-20 and 20-30 cm) collected from Kabul River, Pakistan, in February 2014. The occurrence levels, enantiomer fractions and potential ecological risk of these organochlorine pesticides (OCPs) were evaluated. The total concentrations of ∑HCHs and ∑DDTs in surface sediments ranged from 4.9-23.9 ng g and from 6.4-18.8 ng g (dry weight basis), respectively. The verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Upstream sites on the Swat River were <LOD. In addition, many legacy pesticides used in the region were not included in the present study because they have been previously reported (Aamir et al, 2017; Saad et al, 2017). For example, endosulfan is a commonly used pesticide reported at concentrations up to 166 ng/L in the Indus River (Shaikh et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upstream sites on the Swat River were <LOD. In addition, many legacy pesticides used in the region were not included in the present study because they have been previously reported (Aamir et al, 2017; Saad et al, 2017). For example, endosulfan is a commonly used pesticide reported at concentrations up to 166 ng/L in the Indus River (Shaikh et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of contaminant studies in Pakistan have focused on metals and pesticides in portions of the Indus River basin downstream of Khyber Pakhtunkhwa in Sindh Province (Mirbahar et al, 2020;Scheurell et al, 2009) or Punjab Province (Ashfaq et al, 2016(Ashfaq et al, , 2019Ashfaq, Khan, et al, 2017;Ashfaq, Noor, et al, 2017;Riaz et al, 2023). In the Khyber Pakhtunkhwa, prior contaminant studies focused primarily on metals in the Kabul (Ali & Khan, 2018;Aamir et al, 2017;; M. I. T.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecotoxicological risk assessment refers to the effective prediction of the possible ecological effects caused by toxic pollutants in the environmental media and the method of assessing the probability of risk occurrence. Contaminated sediments can pose potential ecological risks to the aquatic ecosystem [32]. In this study, a level-screening ecotoxicological risk assessment was conducted using two international sediments quality guidelines (SQGs), the threshold effects level (TEL), probable effects level (PEL) guidelines proposed by Macdonald et al (1996) [33], and the effects rangelow value (ERL), effects range-median value (ERM) guidelines proposed by Long et al (1995) [34].…”
Section: Ecotoxicological Concern Of Ocps In the Sediment Corementioning
confidence: 99%